THE EFFECT OF ACCOUNTING CONSERVATISM, EARNINGS MANAGEMENT AND DEBT MATURITY ON COMPANY FINANCIAL PERFORMANCE - Fitriani, Azizah (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2025)
ABSTRACT It seeks to find